The role of Islamic Philosophy of education in aspiring holistic learning. - Hassan, Aminuddin; Suhid, Asmawati; Zainal Abiddin, Norhasni; Ismail, Habsah; Hussin, Haziyah (Elsevier, 2010)
There is no doubt that looking at the process of learning and also any current scenario in this country is something that should be closely related to what and how someone should know from the view of Islamic Philosophy. Therefore, the nature of education based on Islam itself has the very significant contribution towards human’s life. Discussing Islamic Philosophy of Education will focus on what philosophy is as a core of any theoretical and practical elements of all aspects and knowledge. The philosophical approach is discussed from the perspective of Islam. Then, this writing looks at how Islamic Philosophy tends to mould education in the entire of situation. The discussion of Islamic Philosophy of Education needs to be understood wisely in order to relate it with the context of learning process, and other related situations around us. In this regard, this writing also looks on how the branches of philosophy (such as metaphysics and axiology) and school of thought of philosophy (such as pragmatism) is relevan in discussing Islamic Philosophy of Education. In the end, it is seen as important towards achieving holistic learning. Then this understanding of Islamic Philosophy is proven as important in understanding any current senario in the context or our society in this country, among others are on how the implementation of the aspect of Islamic Philosophy of Education is important in viewing the social problem; the implementation of the aspect of Islamic Philosophy of Education in viewing the Environmental Problem; and the aspect of Islamic Philosophy of Education in Viewing the Emotional and Spiritual Intelligences in current society.